2022
DOI: 10.7759/cureus.28289
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Different Surgical Treatments for Complex Anal Fistula: A Systematic Review

Abstract: Fistula-in-ano is a common proctological condition that primarily affects younger people and leads to chronic morbidity. An anal fistula is divided into simple and complex fistulas. A complex fistula is a challenging problem due to higher recurrence rates and incontinence associated with surgery. Many new methods have been developed for the closure of complex fistula-in-ano, but there is no single best method. The aim of this study is to identify a superior surgical technique for treating complex/high cryptogl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
1
3
0
2
Order By: Relevance
“…This method had the lowest failure and fecal incontinence complication rates. This result was comparable to that of a systematic review by Zahra et al (2022) [ 28 ], which found that closure of the intersphincteric fistula tract was a novel and potentially effective treatment for complex anal fistulas. However, the authors of this review could not recommend those findings because of insufficient data.…”
Section: Discussionsupporting
confidence: 88%
“…This method had the lowest failure and fecal incontinence complication rates. This result was comparable to that of a systematic review by Zahra et al (2022) [ 28 ], which found that closure of the intersphincteric fistula tract was a novel and potentially effective treatment for complex anal fistulas. However, the authors of this review could not recommend those findings because of insufficient data.…”
Section: Discussionsupporting
confidence: 88%
“…Although contrast-enhanced CT can help establish the diagnosis, MRI with enterography may have more clinical utility in pCD patients due to its ability to assess for pCD treatment response and detect concurrent active pCD and fistulas [10] . Patients with pCD may undergo surgeries such as LIFT and endorectal flap advancement surgeries for complex anal fistula treatment [11] . The risk of developing a perineal hernia as a long-term outcome of these procedures is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, decellularized dermal matrix tamponades have been widely used in the treatment of anal fistula. In addition, with the continuous development of 3D bioprinting technology and the application of biological scaffold materials, new ideas have been opened for the treatment of anal fistula by tissue engineering. …”
Section: The Application Of Decellularized Scaffolds In Tissue Engine...mentioning
confidence: 99%